2020
DOI: 10.1590/1981-7746-sol00263
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de sintomas de depressão em agentes comunitários de saúde

Abstract: Resumo Os agentes comunitários de saúde são imprescindíveis e considerados atores importantes para a organização do Sistema Único de Saúde. Este estudo teve como objetivo avaliar a prevalência de sintomas de depressão relacionada aos fatores ocupacionais, sociodemográficos e de estilo de vida dos agentes. Realizou-se um estudo transversal com 400 agentes comunitários, por meio de entrevistas individuais em unidades básicas de saúde de um município situado em Minas Gerais, entre 2015 e 2017. A variável … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
19

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 27 publications
1
15
0
19
Order By: Relevance
“…Higher prevalence of inadequate work ability was found in studies conducted with CHWs in the municipality of Uberaba, also in Minas Gerais state, 3 and in João Pessoa, the capital city of the state of Paraíba; 10 In both studies, more than half of the CHWs studied showed impaired work ability. 3 , 10 A study carried out among CHWs in Juiz de Fora, Minas Gerais state, 6 and another in Pato Branco, state of Paraná, 22 the latter conducted with workers in the furniture industry, also showed high prevalence levels of the WAI. 6 ,22 In the context of primary health care, CHWs stand out as one of the professional categories responsible for preventive and health promotion actions, strengthening the bond between the population and services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher prevalence of inadequate work ability was found in studies conducted with CHWs in the municipality of Uberaba, also in Minas Gerais state, 3 and in João Pessoa, the capital city of the state of Paraíba; 10 In both studies, more than half of the CHWs studied showed impaired work ability. 3 , 10 A study carried out among CHWs in Juiz de Fora, Minas Gerais state, 6 and another in Pato Branco, state of Paraná, 22 the latter conducted with workers in the furniture industry, also showed high prevalence levels of the WAI. 6 ,22 In the context of primary health care, CHWs stand out as one of the professional categories responsible for preventive and health promotion actions, strengthening the bond between the population and services.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are associated with work ability, including sociodemographic characteristics, 2 , 6 health status, 7 behavioral, 6 , 8 , 9 and clinical characteristics, 7 , 6 , 10 work conditions and organization. 6 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para a análise dos sintomas depressivos foi utilizado o Questionário sobre a saúde do paciente -9 (Patient Health Questionnaire -9), o qual permite avaliar indícios de depressão durante os últimos 14 dias por meio de nove perguntas. Neste estudo foi considerada a pontuação ≤ 9 sem sintomas de depressão e > 9 para a presença de sintomas depressivos (Moura et al, 2020).…”
Section: Instrumentosunclassified
“…On the other hand, CHWs are exposed to many adverse factors in their work, which have been shown to compromise their mental health, sometimes to the point of requiring sick leave 10,11,12 . One such factor, localized violence, affects work routine 1,13 , which, in turn, can affect the CHW's mental health 12 .…”
Section: Introductionmentioning
confidence: 99%